High-frequency ultrasonography (HFUS) as a useful tool in differentiating between plaque morphea and extragenital lichen sclerosus lesions - Białynicki-Birula, Rafał; Reszke, Radomir; Szepietowski, Jacek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Morphea and lichen sclerosus (LS) are chronic inflammatory diseases that may pose a diagnostic challenge for a physician. High-frequency ultrasonography (HFUS) is a versatile diagnostic method utilized in dermatologic practice, allowing monitoring the course of the disease, treatment response and differentiation between certain skin disorders. Aim : To prove the usefulness of HFUS in differentiating between plaque morphea and extragenital LS lesions. Material and methods : We examined 16 patients with plaque morphea and 4 patients with extragenital LS using 20 MHz taberna pro medicum TM (Germany) device. Results : Investigations revealed hyperechogenic entrance echo in both morphea and LS lesions, whereas a distinct polycyclic surface of the entrance echo was detected exclusively in LS. Conclusions : High-frequency ultrasonography is a current diagnostic modality that may prove useful in differentiating between morphea and LS lesions.